Agroecological urban agriculture - strategy for health promotion and food and nutrition security - doi: 10.5020/18061230.2012.p381 - Silvana Maria Ribeiro; Elaine de Azevedo; Maria Cecília Focesi Pelicioni; Cláudia Maria Bógus; Isabel Maria Teixeira Bicudo Pereira (Universidade de Fortaleza, 2012)
Objective: To raise considerations about the agroecological urban agriculture, in articulation with movements for promotion of health and food and nutrition security, with participation of local communities. Data synthesis: Documental research carried out through the reading and analysis of report, field activities' records, participants' testimonies and interview performed with the project coordinator. The contribution of agroecological urban agriculture was perceivable in regard to the community protagonism, popular participation, and the rising of feeding and environmental awareness among social actors. Conclusion: Relevant aspects in consonance with the principles and fields of action of Health Promotion were identified, especially the strengthening of intersetorial actions, the local community empowerment, individual and collective protagonism, creation of health-friendly environments and community mobilization.